FORMULASI PERMEN JELI SARI BUAH SINGI (Dillenia serrata Thunbr) KOMBINASI MADU MENGGUNAKAN GELATIN - Nirwati Rusli (Jurnal Ilmiah Farmasi Farmasyifa, 2018)
Singi fruit is a fruit that contains citric acid compound vitamin C and beta carotene which can have an effect for health. Honey nutritious produce energy, increase endurance and stamina. Gelatin as gelling agent can produce the chewy candy. This research aims to make preparations jelly candy fruit juice Singi honey combination using gelatin and gelatin choose the most optimum concentration and see if candy is unfit for consumption. Research conducted experiment, the sample series then made into 3 formulas with gelatin concentration variation 9%, 10% and 11%. The results showed that the candy is made of orange-brown, distinctive smell, with a sweet and sour taste and chewy texture. Preparations candy jelly with gelatin optimum concentration is candy with a concentration of 10% gelatin. Microbiological test results showed that the jelly candy qualify Total Plate Count is 3 x 103 and Figures Fungus Yeast 1 x 102 qualified food SNI namely Total Plate Count 3 x 103 and Figures Fungus Yeast 1 x 102